EVALUASI PENGELOLAAN PRAKTIK KERJA INDUSTRI (PRAKERIN) DI SMK NEGERI 1 SIAK KECAMATAN SIAK KABUPATEN SIAK - DASTIAN SUSILA; ZULFAN SAAM; DAENG AYUB NATUNA (Universitas Riau, 2017)
Practical Industry program on vocational school should be implemented basedon major and every school needful. Every year all of vocational school implemented the practicalindustry so that is automatically help many industrial company.The management of practicalindustry is handled by school it self so it is become a must to take a research on to the managementevaluation through practical industry.The research ‘s goal is to mention and clearly analyzethrough some aspect as follows : (1) to get information and analysis through program planning.(2) to get information and analysis through program organizing (3) to get information andanalysis through program actuting (4) to get in5formation and analysis through programcontrolling. This research use evaluative method with documentation evaluation, observation,and interviews. The research conducted at SMK N 1 SIAK which located on Jalan TengkuBuwang Asmara No 2 Siak regency, Siak district. The research has been taken for 3 month,starting from October until December 2016.The evaluation model which use on the researchwas CIPP, it contains of Context evaluation (C ), Input (I), Process (P), and Product (P). CIPPmodel was adopted on to the research related to the needful on evaluation otherwise producescoring which usually called probation.Planning through management of practical industry whichhas been done at SMK N 1 Siak based on effectiveness standard by good result. The result ofevaluation related organizing throng management practical industry get a very well result basedon effectiveness standard. Refers to the result of planning and organizing shows that evaluationthrough implementation of the practical industry program was good. Theresult related last subfocusabout controlling evaluation in management through practical industry were showing avery good activity. In short, the evaluation of management practical industry as hole researchwere showing good result, beside it need to be improved to get best result as the expectation.